The Determinants of successful uptake of life assurance products – A Literature Review - Kodia, Janepher G. K. (Australian Journal of Business Science Design & Literature, 2017)
The consumption of life assurance products globally is said to be influenced by several broad factors, including socio-economic, demographic, political and internalization, among others. Generally, the consumption levels of life assurance products have not been impressive. In most cases the incepted life assurance policies end up lapsing and therefore fail to meet the intended purpose. This paper explores the historical background of insurance in general and specifically, life assurance in Kenya. It reviews both the theoretical as well as previous empirical studies in an effort to assess the determinants of life assurance consumption in Kenya.
Keywords: Life assurance demand; rationality; self-interest; utility maximization; prospect; human life value; uptake level; insurance; risk; distribution channels